The Role of Non-coding RNAs in Alzheimer’s Disease: From Regulated Mechanism to Therapeutic Targets and Diagnostic Biomarkers - Zhang, Yuan; Zhao, Yanfang; Ao, Xiang; Yu, Wanpeng; Zhang, Lei; Wang, Yu; Chang, Wenguang (Frontiers in Aging Neuroscience, 2021)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder. AD is characterized by the production and aggregation of beta-amyloid (Aβ) peptides, hyperphosphorylated tau proteins that form neurofibrillary tangles (NFTs), and subsequent neuroinflammation, synaptic dysfunction, autophagy and oxidative stress. Non-coding RNAs (ncRNAs) can be used as potential therapeutic targets and biomarkers due to their vital regulatory roles in multiple biological processes involved in disease development. The involvement of ncRNAs in the pathogenesis of AD has been increasingly recognized. Here, we review the ncRNAs implicated in AD and elaborate on their main regulatory pathways, which might have contributions for discovering novel therapeutic targets and drugs for AD.